Embolization therapy for benign prostatic hyperplasia: Influence of embolization particle size on gland perfusion. Issue 2 (12th December 2012) - Brook, Olga Rachel; Faintuch, Salomao; Brook, Alexander; Goldberg, S. Nahum; Rofsky, Neil M.; Lenkinski, Robert E.
<x xml:space="preserve">Abstract</x> Purpose To assess the influence of embolic size on the therapy response of prostatic arterial embolization (PAE) based on perfusional changes seen on dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI). Materials and Methods Twelve beagles underwent PAE, four dogs with each particle size: A: 100–300 μm; B: 300–500 μm; and C: 500–700 μm. Prior to and 1 month after the embolization all dogs underwent prostate DCE MRI. Results After embolization, time to maximal perfusion intensity for prostate parenchyma increased in B (188 vs. 135 sec, P = 0.023) and C (200 vs. 120 sec, P = 0.001), while it did not change for A (139 vs. 124 sec, P = 0.39). The maximal relative intensity increased after embolization in C (3.84 vs. 2.38, P < 0.001), while it did not change for A (2.50 vs. 2.44, P = 0.36) and B (3.23 vs. 2.9, P = 0.21). The extent of visualized intraprostatic urethral wall increased after embolization in B compared with A and C, 239.5 ± 138.1% vs. 56.1 ± 34.3, P = 0.04. Enhancement changes correlated with prostate volume changes: prostate volumes in A decreased less as compared with B and C (77 ± 34% vs. 56 ± 14%), P = 0.02. Conclusion The enhancement and morphological data are useful to monitor response to therapy after embolization. Embolization with 300–500 and 500–700 μm particle may provide better results than with 100–300 μm particles in a canine model. J. Magn. Reson. Imaging 2013;38:380–387. © 2013 Wiley Periodicals, Inc.